DOI: 10.11606/d.41.2016.tde-14012016-161218
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids as inductors of ovulation in Astyanax altiparanae (Characiformes: Characidae) during artificial reproduction

Abstract: Stress can be defined as a condition in which the dynamic equilibrium of the body is disturbed and several studies have demonstrated the action of some corticosteroids modulating stress situations, such as reproduction. However, the role of corticosteroids in fish reproduction can be either positive or deleterious, depending on many variables. In the Astyanax genus, the same stress stimulus can successfully induce the reproduction in Astyanax altiparanae, but not in other species of the same genus. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In contrast, animals from the control group, but maintained at 20°C showed higher plasma concentration of MIS when compared to animals injected with saline, and spawned, probably due to some physiological trigger not evaluated in this study, which could be related to stress axis (brainpituitary-interrenal) which is also related with reproduction (Milla et al, 2009). Previous studies showed that A. altiparanae exposed to high densities and high water renewal spawn spontaneously without hormonal induction, during the spring and summer period (Chehade et al, 2015) and shows an increase in plasma cortisol concentration, exhibiting the so-called stress induced spawning (Parreira, 2015).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast, animals from the control group, but maintained at 20°C showed higher plasma concentration of MIS when compared to animals injected with saline, and spawned, probably due to some physiological trigger not evaluated in this study, which could be related to stress axis (brainpituitary-interrenal) which is also related with reproduction (Milla et al, 2009). Previous studies showed that A. altiparanae exposed to high densities and high water renewal spawn spontaneously without hormonal induction, during the spring and summer period (Chehade et al, 2015) and shows an increase in plasma cortisol concentration, exhibiting the so-called stress induced spawning (Parreira, 2015).…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies showed that A . altiparanae exposed to high densities and high water renewal spawn spontaneously without hormonal induction, during the spring and summer period (Chehade et al, 2015) and shows an increase in plasma cortisol concentration, exhibiting the so‐called stress induced spawning (Parreira, 2015).…”
Section: Discussionmentioning
confidence: 99%